Peran Muallaf Center Dalam Pembinaan Keagamaan Muallaf Di Yogyakarta - stainu, ghazali; Hidayat, Topan (STAINU Purworejo, 2018)
This study aims to determine how the adjustment in the conversion of aconvert. Subjects were reverts Center Yogyakarta. This study is a qualitativeresearch with phenomenological approach. Data obtained and collected throughsemi-structured interviews and observations by using interview guidelines and achecklist. Then, the data is analyzed using data reduction, display / presentationof data and make inferences / verification interactive model of Miles & Huberman(1984). The results showed that the problems experienced by a convert CenterYogyakarta is family issues, career and employment, and marginalized by society.The individual who has religious conversions